2021
DOI: 10.1007/s11523-021-00816-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of p53 Expression in Patients with RAS/BRAF Wild-Type Metastatic Colorectal Cancer Receiving Irinotecan and Cetuximab as Later Line Treatment

Abstract: Background Preclinical and clinical data indicate that p53 expression might modulate the activity of the epidermal growth factor receptor (EGFR), influencing response/resistance to anti-EGFR monoclonal antibodies. However, the association between p53 status and clinical outcome has not been clarified yet. Objective In our study, we evaluated the role of p53 expression in patients with RAS/BRAF wild-type metastatic colorectal cancer (mCRC) receiving irinotecan/cetuximab in an exploratory and a validation cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Today, anti-angiogenic treatment represents a cornerstone of mCRC patient management in both the first-and second-line settings [3][4][5][6][7][8][9][10][11][12]. Unfortunately, the real OS gain from bevacizumab, aflibercept, and ramucirumab emerged from clinical trials and reallife data is about 1.4 to 1.6 months, which is quite marginal in the clinical history of a mCRC patient [3][4][5][6][7][8][9][10][11][12]16,17,[116][117][118][119]. The same concept applies even more to the role of regorafenib in further lines of treatment [20,120].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, anti-angiogenic treatment represents a cornerstone of mCRC patient management in both the first-and second-line settings [3][4][5][6][7][8][9][10][11][12]. Unfortunately, the real OS gain from bevacizumab, aflibercept, and ramucirumab emerged from clinical trials and reallife data is about 1.4 to 1.6 months, which is quite marginal in the clinical history of a mCRC patient [3][4][5][6][7][8][9][10][11][12]16,17,[116][117][118][119]. The same concept applies even more to the role of regorafenib in further lines of treatment [20,120].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the standard of care for mCRC treatment is represented by first-line fluoropyrimidine-based chemotherapy, either single agent or in combination with oxaliplatin or irinotecan (doublet or triplet regimen), plus biological agents targeting either vascular endothelial growth factor (VEGF, bevacizumab) or epidermal growth factor receptor (EGFR, panitumumab or cetuximab). The treatment plan is chosen according to the mutational/molecular status of the tumor and the clinical features of the patient [7,8]. Immunotherapy with immune-checkpoint inhibitors (pembrolizumab) is restricted to mCRC patients with mismatch-repair deficiency (dMMR) or high microsatellite instability (MSI-H) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, mutations in other key oncogenic genes also affect cancer cell functions and response to therapies. For example, mutations in PIK3CA and TP53 occur often in CRC and are also suggested to render mCRC resistant to EGFR targeted therapies [47][48][49][50] . Speci cally, PIK3CA mutations lead to activation of PI3K, another key mediator in RTK signaling pathways including HER3 49,51 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to KRAS and PIK3CA mutations, CRC cells used in this study harbored mutations in TP53. Preclinical studies suggested that there are correlations between resistant to therapies and TP53 alterations in mCRC [40][41][42] . Our results showed that liver ECs induced HER3-AKT activation and cell survival in all cell lines we used, which harbor either wild-type or mutant TP53.…”
Section: Discussionmentioning
confidence: 99%